Integration of RFID and WSN for Supply Chain Intelligence System - Mirshahi, Shiva; Uysal, Sener; Akbari, Aliakbar (IEEE, 2013)
Radio Frequency Identification (RFID) system is used for detecting and identifying the tagged objects by electromagnetic signals. Wireless Sensor Networks (WSN), which consists of a huge numbers of nodes, can monitor the condition of the environment including pressure, humidity, and temperature. Data is transferred via nodes to a certain location. Integration of RFID and WSN provides a new feature and improves their functionalities. In the RFID system, each tag can only communicate with a reader. By integrating RFID tags with nodes, communication of the RFID tags with each other is possible and also integration of readers with nodes facilitates negotiation of readers together. The RFID and WSN integration in supply chain provides system intelligence. In such a case, tag is embedded in objects and reader is integrated with nodes. Therefore, identification and detection of tagged items is provided by using RFID and monitoring of environment can be obtained by using WSN. The present case study is simulated in the Petri Net Toolbox in MATLAB environment. It represented the negotiation of smart devices spontaneously in managing variety of instructions in order to enhance system performance.
International Conference on Electronics, Computers and Artificial Intelligence(ECAI) -- JUN 27-29, 2013 -- Univ Pitesti, Pitesti, ROMANIA
Keywords: Radio frequency identification; wireless sensor networks; integration of RFID and WSN; supply chain management; Petri net